(3TQM GdebGeGJ GdMQjQjIs - (3GHf XaQ GdUbdj , CHi YHO Gddg eMeO Hf YHO dGdgs; (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s ((3eMeO Hf CHj GdeLO Hf YHO GdZaGQ GdJejei GdSgQhQOi s)
(3ChdgG (B:s
(3hGdMeO ddg QH GdYGdejf hHYO aEfc SCdJfi CjgG GdCN GdQTjO TQM eG JTJed Ydjg GdebGeGJ s
(3BNQgG (B:s
(3GdJQGbi LeY JQbhI Ydi hRf aYdhI hgj YXe Hjf KZQI GdfMQ hGdYGJb Je TQM GdebGeGJ Ydi MSH GdLgO hGdMeO ddg QH GdYGdejf s
(3HChdgG agQS HNW eZGjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs